Perbandingan Efektivitas Seduhan Kulit Nanas (Ananas Comosus) Dengan Temephos 1% Sebagai Biolarvasida Nyamuk Culex sp - Benaya Yamin Onesiforus; Elisa Rinihapsari; Devi Fatmasari (Jurnal Anestesi, 2023)
Culex mosquitoes are vectors of diseases such as Japanese encephalitis, St. Louis encephatis, West Nile Virus and Filariasis. Culex quinquefasciatus is an example of mosquito species which is role as vector of filariasis. Indonesia suffered health issue due to mosquito-borne disease in each year. Larvacides application is one of the most effective method to control mosquitoes spread. Larvicides can be either synthetic or natural. One of the natural materials that can be used as larvicide is pineapple peel. This study objective was to compare the effectiveness of pineapple peel and temephos 1% in killing mosquito larvae. This type of research is experimental with purposive sampling technique. Data were analyzed using Kruskal Wallis statistical test and Mann Whitney posthoc test. The results indicate a significant difference (p<0.05) in effectiveness between temephos and pineapple peel steeping concentration with temephos 1% has better the effectiveness as mosquitoes larvicide than pineapple peel steeping..